Anticipating the Need for New Skills for the Future Aerospace and Aviation Professionals - Lappas,Ilias (2016)
ABSTRACT This study aims to translate needed future skills to the university classroom for the aerospace and aviation industry personnel, given the fast-paced change taking place in both the industry and the education sectors. A synopsis of the current challenges faced in the educational field is outlined, followed by a mapping of the future of both education and air platforms, in an attempt to set the basis of the needed skills framework. The Assessment and Teaching of 21st Century Skills Project is used as a baseline for the definition of the future “critical” skill set, which is considered well aligned with the future needs of the aerospace industry. It is suggested that this critical skill set can be translated to the higher education environment through an effective redesign of the existing teaching and learning philosophy and the practices.